Study on factors influencing college students’ digital academic reading behavior - Chang, Liyan; Wang, Yujie; Liu, Jing; Feng, Yao; Zhang, Xinyao (Frontiers in Psychology, 2023)
Purpose-The study explores the internal factors and external environmental factors on the influencing mechanism of their behavioral intention and use behavior of digital academic reading, and analyzes the relationship between behavioral intention and use behavior, so as to provide a basis for schools to cultivate students' academic reading literacy and optimize the current digital academic reading environment. Design/methodology/approach- The determinants used in this paper are adopted from Structural Equation Model (SEM). The quantitative study adjusted the explanatory variables according to the characteristics of the field of digital academic reading and constructed a new college students' digital academic reading information behavior model (DACB). SPSS and AMOS are used to analyze the survey data. Findings- Effort expectancy (EE), social influence (SI), price value (PV), perceived risk (PR) and habit (BH) have a significant impact on behavioral intention (BI), and behavioral intention (BI) and habit (BH) have a significant effect on use behavior (B). However, performance expectancy (PE) and facilitating conditions (FC) have no significant effect on use behavior (B). Originality/value- The findings of this study will contribute to a better understanding of the influencing factors of Chinese college students’ digital academic reading behavior. This study will provide a basis for improving the academic reading literacy program in colleges and optimize the current digital academic reading environment.